2015
DOI: 10.31686/ijier.vol3.iss12.490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Women Candidatures and Outcomes in the 2011 and 2015 Nigeria General Elections

Abstract: One noticeable development in the Nigeria’s 2015 general elections is the differentials in the numbers and outcomes of women involvement as candidates in comparison to the 2011 elections. The percentage of women contesting for presidential position decline from 12.5% in 2011 to 7.1% in 2015. That of the gubernatorial election also witnessed a reduction from 10.2% in 2011 to 7.1% in 2015, while the percentage of women for deputy governorship positions was relatively stable with only an increase of 0.4%. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…With leaves being the major photosynthetic organ of plants, it is indicative that rate of photosynthesis for seedlings growing in diesel and spent engine oil contaminations were reduced and thus slowing down growth (Olajuyigbe and Sijuola, 2015). The seedling growth variables reduced with increase in contamination levels confirming the assertion that the limitation of growth by hydrocarbon derivatives is dose dependent (Idowu and Fayinminnu, 2015). In this study, seedling height, collar diameter and leaf production were all limited by increase in diesel and spent engine oil contamination levels.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…With leaves being the major photosynthetic organ of plants, it is indicative that rate of photosynthesis for seedlings growing in diesel and spent engine oil contaminations were reduced and thus slowing down growth (Olajuyigbe and Sijuola, 2015). The seedling growth variables reduced with increase in contamination levels confirming the assertion that the limitation of growth by hydrocarbon derivatives is dose dependent (Idowu and Fayinminnu, 2015). In this study, seedling height, collar diameter and leaf production were all limited by increase in diesel and spent engine oil contamination levels.…”
Section: Discussionsupporting
confidence: 76%
“…Hence, there is need for empirical information on the phytoremediation qualities of tropical trees, particularly hardy species that are known to survive and thrive under difficult conditions. Previous studies have shown the phytoremediation potentials of tropical species such as Gmelina arborea (Alamu et al, 2012); Treculia africana (Agbogidi et al, 2011); Moringa oleifera (Agbogidi and Ilondu, 2013); Terminalia ivorensis (Olajuyigbe and Sijuola, 2015), Khaya senegalensis and Terminalia superba (Olajuyigbe and Aruwajoye, 2014), and Jatropha curcas (Idowu and Fayinminnu, 2015).…”
Section: Introductionmentioning
confidence: 99%